دور التخطیط السیاحي البیئي في استدامة المناطق الأثریة: دراسة حالة منطقة أهرامات الجیزة - یحیي شحاته , الزق (Finance and Business Economies Review, 2018)
No doubt that environmental tourism planning is one of the methods that have recently emerged to manage and develop archaeological sites, improve the level of services provided in those sites, preserve their environment from degradation and hence sustainability. Therefore, this research aims to shed light on the concepts of environmental tourism planning and the concepts of sustainability of archaeological sites. In addition to, this study is an application to one of the important tourist attractions in Egypt, the area of the pyramids of Giza, and the study reached the importance of environmental tourism planning to achieve the sustainability of archaeological areas and the need to enact laws and legislation that contributes to achieving this and coordination between the ministries concerned, each with regard to the integration of the public and the sustainability of archaeological areas.